Joyful learning in kindergarten - Fisher, Bobbi; Fisher, Bobbi (Portsmouth, NH : Heinemann, 1998)
The author, a whole language kindergarten teacher, outlines her beliefs about how children learn; offers discussions of whole language theory and application, especially in the area of language arts; and includes bibliographies, and an appendix in which teachers share their successful classroom strategies.
Rev. ed. of: Joyful learning. c1991.
Includes bibliographical references (p. 274-292) and index.
Professional
Keywords: Kindergarten -- Curricula; Language arts (Preschool); Language experience approach in education; Reading (Preschool) -- Language experience approach; Kindergarten -- Curricula; Language arts; Reading; Whole language